Website-based Scratch Media Improves Cognitive Learning Outcomes in Science for Junior High School Students: Media Scratch Berbasis Website Meningkatkan Hasil Belajar Kognitif IPA Siswa SMP - Latif, Ahmad Adil; Shofiyah, Noly (Indonesian Journal of Education Methods Development, 2025)
General Background: Science education plays a critical role in developing students’ cognitive abilities, requiring engaging and interactive learning media to optimize outcomes. Specific Background: In many Indonesian junior high schools, conventional methods such as textbooks and PPTs often fail to fully support students’ comprehension, particularly in topics like ecology and biodiversity. Knowledge Gap: Limited research has examined the application of Scratch, a website-based visual programming platform, in science learning at the junior high school level. Aims: This study aims to investigate the use of website-based Scratch media in improving the cognitive learning outcomes of seventh-grade students. Results: Using a quasi-experimental design with random sampling, two classes were assigned different media: Scratch for the experimental group and PPT for the control group. Analysis using the Independent Sample T-Test showed a significant difference (p = 0.039) in N-Gain scores, with the experimental group achieving 0.56 (medium) compared to the control group’s 0.41 (medium). Novelty: This research uniquely applies Scratch to junior high school science topics, offering an interactive approach to abstract concepts. Implications: Findings suggest Scratch can be an effective alternative to traditional media, fostering active participation and deeper understanding in science learning. Highlights : Website-based Scratch outperformed PPT in improving cognitive outcomes. Significant N-Gain score difference between experimental and control groups. Novel application of Scratch to ecology and biodiversity topics at SMP level. Keywords: Science Education, Scratch, Cognitive Learning Outcomes, Junior High School, Website-Based Learning